2017
DOI: 10.1016/j.kint.2016.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Human vascular progenitor cells derived from renal arteries are endothelial-like and assist in the repair of injured renal capillary networks

Abstract: Vascular progenitor cells show promise for the treatment of microvasculature endothelial injury. We investigated the function of renal artery progenitor cells derived from radical nephrectomy patients, in animal models of acute ischemic and hyperperfusion injuries. Present in human adventitia, CD34positive/CD105negative cells were clonal and expressed transcription factors Sox2/Oct4 as well as surface markers CXCR4 (CD184)/KDR(CD309) consistent with endothelial progenitor cells. Termed renal artery-derived vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 46 publications
(49 reference statements)
1
49
0
Order By: Relevance
“…The main miRNAs involved in renal protection from IRI, type of secreting cell, and mechanisms of action are outlined in Table 3 (172)(173)(174)(175)(176)(177)(178)(179)(180)(181).…”
Section: Extracellular Vesicles As a Therapeutic Tool In Renal Transpmentioning
confidence: 99%
“…The main miRNAs involved in renal protection from IRI, type of secreting cell, and mechanisms of action are outlined in Table 3 (172)(173)(174)(175)(176)(177)(178)(179)(180)(181).…”
Section: Extracellular Vesicles As a Therapeutic Tool In Renal Transpmentioning
confidence: 99%
“…Recent study revealed that EVs‐derived bioactive molecules from different cell sources promote endothelial regeneration. Following treatment of injured endothelial cells with renal artery‐derived vascular progenitor cells (RAPC)‐derived exosomes, endothelial migration improved and stimulates a reparative phenotype . MPs derived from kidney‐derived mesenchymal stem cells (KMSCs) have been reported to ameliorate rarefaction of peritubular capillaries (PTC) in ischaemic kidneys via delivery of proangiogenic effectors.…”
Section: Evs‐mediated Intranephron Communicationmentioning
confidence: 99%
“…Following treatment of injured endothelial cells with renal artery-derived vascular progenitor cells (RAPC)-derived exosomes, endothelial migration improved and stimulates a reparative phenotype. 67 For example, urinary EV UMOD mRNA levels are progressively elevated from T2DM to DKD groups and correlate with eGFR and ACR levels. 71 We have recently isolated exosome released from podocyte in the urine, the vesicle structure was positive for the markers of both exosome and podocyte, CD9, AQP2 and nephrin.…”
mentioning
confidence: 99%
“…In an animal model of renal ischemia/reperfusion (I/R) injury, Pang et al investigated renal artery-derived progenitor cells (RAPC) (defined as CD34+/CD105-cells) obtained from human renal arterial adventitia of radical nephrectomy specimens [73]. RAPC were found to have EPC–like characteristics.…”
Section: Epc Studies In Various Disease Modelsmentioning
confidence: 99%